Impact of one year judo training on body symmetries in youth judokas - Kambic, T.; Vukovic, R. S.; Vukovic, L.; Simenko, J. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background and Study Aim: Anthropometric status of youth judokas is an important factor in the process of maturation and sport development from cadet to senior judo athletes. Training process influences the body in different proportions, therefore a regular screening is recommended to monitor the youth athlete development and to give regular feedback to coaches about their training plans. The aim of present study was the status of the body symmetries in youth judokas during one year training period.